The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1002/hed.23573
|View full text |Cite
|
Sign up to set email alerts
|

Proton therapy for head and neck adenoid cystic carcinoma: Initial clinical outcomes

Abstract: Background: To report outcomes of proton therapy in head and neck adenoid cystic carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 25 publications
3
28
1
Order By: Relevance
“…When an additional dose was added to the skull base using Gamma Knife, 40‐month local control improved to 82% compared to 32% in the cohort who did not have Gamma Knife . Linton et al performed a similar but a shorter‐term analysis among patients with and without skull base involvement with a 2‐year local control rate of 95%, the majority of patients receiving proton therapy alone versus combined proton and photon therapy. Another report by Takagi et al observed a 5‐year local control rate of 76% after proton RT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When an additional dose was added to the skull base using Gamma Knife, 40‐month local control improved to 82% compared to 32% in the cohort who did not have Gamma Knife . Linton et al performed a similar but a shorter‐term analysis among patients with and without skull base involvement with a 2‐year local control rate of 95%, the majority of patients receiving proton therapy alone versus combined proton and photon therapy. Another report by Takagi et al observed a 5‐year local control rate of 76% after proton RT.…”
Section: Discussionmentioning
confidence: 99%
“…5,15,28 Other studies utilizing proton therapy reported comparable or slightly worse toxicity profiles with rare G4 or G5 toxicities, including temporal lobe necrosis, vision loss, bleeding from nasopharyngeal ulceration, and cerebrospinal fluid leak. [15][16][17]29 Severe toxicities were also seen after photon therapy, including visual loss, G4 mucositis, tracheal stenosis, and fistula formation. 12,20 Severe toxicities after neutron therapy included temporal lobe necrosis, paralysis, and fistula formation.…”
Section: Discussionmentioning
confidence: 99%
“…Favorable results have been reported by Zenda et al, who reported high control rates for adenoma, adenoid cystic carcinoma, and melanoma with otherwise low sensitivity to radiation [15]. Linton et al reported that the local control rates for adenoid cystic carcinoma in the head and neck region 2 years after proton beam therapy were 95% in patients receiving initial treatment and 86% in patients with recurrence, exhibiting favorable results [16]. In their study, acute toxicities of grade 2 accepted transient radiation dermatitis in 16, and lateralized mucositis in 7 of 26 patients.…”
Section: Discussionmentioning
confidence: 66%
“…However, this type of therapy has been limited by availability and cost. Moreover, while not mentioned as part of the NCCN Guidelines, proton therapy has also shown utility in tumors involving the skull base and/or with significant invasion along cranial nerves …”
Section: Definitive Rtmentioning
confidence: 99%
“…Moreover, while not mentioned as part of the NCCN Guidelines, proton therapy has also shown utility in tumors involving the skull base and/or with significant invasion along cranial nerves. 74,75 6 | POSTOPERATIVE RT Adjuvant therapy is typically not required for benign tumors. However, pleomorphic adenoma is a unique clinical entity with known risk for recurrence, possibly in a multifocal fashion as a result of close or positive margins, violation of the tumor capsule, or tumor spillage.…”
Section: Definitive Rtmentioning
confidence: 99%